Nursing’s Role in Advance Care Planning for Hispanic / Latino Individuals (2011)
Abstract End-of-life care decisions are challenging for most people and cultural beliefs may facilitate or hinder such decisions. Advance care planning provides a venue to interact with and communicate to healthcare professionals a person’s documented health and medical treatment wishes at end of life. Open communication, cultural accommodation, and mutual understanding among the healthcare provider, patient, and family are key to effective advance care planning. This article discusses how Hispanic / Latino people address end-of-life care and what cultural aspects are especially relevant for this population. The nurse’s role in assisting Hispanics / Latinos with advanced care planning is presented at various levels of the nursing professional spectrum. Key Words: End of Life, Decision Making, Hispanic-Latinos, Nursing, Advance care Planning Resumen Las decisiones relacionadas con las fases terminales de la vida son difíciles para la mayoría de las personas. Las creencias culturales pueden facilitar o dificultar dichas decisiones. La planeación adelantada del cuidado provee el mecanismo para interactuar y comunicarse con los profesionales de la salud sobre los deseos de la persona para el final de su vida. La comunicación abierta, la adaptación cultural, y el entendimiento mutuo entre el proveedor de la salud, el paciente, y la familia son la clave para una planeación adelantada efectiva. Este artículo analiza como la gente Hispano/Latina enfrenta las fases terminales de la vida y qué aspectos culturales tienen una relevancia especial para esta población. El papel del personal de enfermería que trabaja con los Hispano/Latinos en la planeación de las fases terminales de la vida es presentado en los varios niveles profesionales de enfermería. Palabras claves: final de la vida, la toma de decisiones, hispano-latinos, Enfermería, Planificación anticipada de la atención.